2017
DOI: 10.1111/ajag.12479
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the maximising cognition (MAXCOG) information resource for clients with mild cognitive impairment and their families

Abstract: Some family supporters appeared to benefit from using the new resource but people with MCI may require further face-to-face support to learn new strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…A high level of performance bias and insufficient reporting of methods were the major concerns. Twelve studies indicated that no blinding strategy was adopted, [58][59][60][61][62][63][64][65][66][67][68][69] and the others had inadequate documentation of the blinding strategy. [70][71][72][73][74][75][76][77][78] Detection bias was unclear in six studies due to missing assessor blinding status.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…A high level of performance bias and insufficient reporting of methods were the major concerns. Twelve studies indicated that no blinding strategy was adopted, [58][59][60][61][62][63][64][65][66][67][68][69] and the others had inadequate documentation of the blinding strategy. [70][71][72][73][74][75][76][77][78] Detection bias was unclear in six studies due to missing assessor blinding status.…”
Section: Study Selectionmentioning
confidence: 99%
“…[70][71][72][73][74][75][76][77][78] Detection bias was unclear in six studies due to missing assessor blinding status. 59,66,70,[74][75][76] One study 63 did not blind the post-test outcome assessors, resulting in a high risk of detection bias. For selection bias, unclear methods for allocation concealment (n ¼ 11) [59][60][61][65][66][67]69,73,74,76,77 and the generation of random sequences (n ¼ 6) 59,60,65,66,69,76 were reported.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…A manual was developed to encourage consistency between counsellors in implementing the approach. A set of information handouts provided easy access to range of ideas and strategies that could be utilized as part of a face-to-face intervention (Regan & Wells, 2018). The primary outcomes were goal performance and satisfaction.…”
Section: How Effective Is Cognitive Rehabilitation In MCI and Mixed P...mentioning
confidence: 99%